2019
DOI: 10.1021/acs.joc.9b01594
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Heparan Sulfate- and Dermatan Sulfate-Related Oligosaccharides via Iterative Chemoselective Glycosylation Exploiting Conformationally Disarmed [2.2.2] l-Iduronic Lactone Thioglycosides

Abstract: Heparan sulfate (HS) and dermatan sulfate (DS) are l-iduronic acid containing glycosaminoglycans (GAGs) which are implicated in a number of biological processes and conditions including cancer and viral infection. Chemical synthesis of HS and DS is required to generate structurally defined oligosaccharides for a biological study. Herein, we present a new synthetic approach to HS and DS oligosaccharides using chemoselective glycosylation which relies on a disarmed [2.2.2] l-ido lactone motif. The strategy provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Gardiner and co‐workers’ described a novel approach towards the preparation of protected HS oligosaccharides bearing reducing end thioglycoside functionality (Scheme 12). [35] The authors employed a sequential chemoselective glycosylation at the reducing end, additive to their previously reported non‐reducing terminus extension via lactone‐terminated d ‐GlcN‐ l ‐IdoA intermediates [36] . This new approach introduced chemoselective activation of a reducing end l ‐IdoA‐lactone to enable iterative HS oligosaccharide synthesis, without the need to interconvert the reducing end anomeric group.…”
Section: Synthetic Methodology Developments For Heparan Sulfate Synthesismentioning
confidence: 99%
“…Gardiner and co‐workers’ described a novel approach towards the preparation of protected HS oligosaccharides bearing reducing end thioglycoside functionality (Scheme 12). [35] The authors employed a sequential chemoselective glycosylation at the reducing end, additive to their previously reported non‐reducing terminus extension via lactone‐terminated d ‐GlcN‐ l ‐IdoA intermediates [36] . This new approach introduced chemoselective activation of a reducing end l ‐IdoA‐lactone to enable iterative HS oligosaccharide synthesis, without the need to interconvert the reducing end anomeric group.…”
Section: Synthetic Methodology Developments For Heparan Sulfate Synthesismentioning
confidence: 99%
“…The anomeric thioglycoside of β- 154 was not activated under NIS/AgOTf activating conditions, thereby allowing the synthesis of lactone-containing disaccharide 156 via chemoselective activation of glucoazide thioglycoside 155 . It was later shown that α- 154 was also unreactive under the same conditions with both 2-azido- and 2-trichloroacetyl-protected thioglycoside donors . This phenomenon was exploited in 2019 for the development of a strategy for the synthesis of heparan- and dermatan-sulfate-related oligosaccharides using this conformationally disarmed [2.2.2] l -iduronic lactone motif as a conformational switch to control reactivity (Scheme b) .…”
Section: Glycosylations Using Torsionally Disarmed Glycosyl Donorsmentioning
confidence: 99%
“…111 The anomeric thioglycoside of β-154 was not It was later shown that α-154 was also unreactive under the same conditions with both 2-azido-and 2-trichloroacetylprotected thioglycoside donors. 112 This phenomenon was exploited in 2019 for the development of a strategy for the synthesis of heparan-and dermatan-sulfate-related oligosaccharides using this conformationally disarmed [2.2.2] Liduronic lactone motif as a conformational switch to control reactivity (Scheme 24b). 112 Chemoselective activation of monocyclic iduronate thioglycoside disaccharides 158 and 161 could be performed over the anomeric thioglycosides of bicyclic [2.2.2] L-ido lactone containing acceptors α-157 or α-160, respectively.…”
Section: Glycosylations Using Torsionallymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the structural diversity of HS, well-defined compounds cannot be obtained from natural sources. Several laboratories have successfully prepared HS oligosaccharides and, although elegant, these approaches are mainly focused on the preparation of compounds composed of the same repeating unit. The enzyme-mediated synthesis of HS oligosaccharides requires significantly fewer steps but cannot provide a wide variety of structures due to the promiscuity of the biosynthetic enzymes. As a result, structure–activity relationship studies have employed small numbers of HS oligosaccharides that cannot properly probe the ligand selectivities of HS-binding proteins. ,, …”
Section: Introductionmentioning
confidence: 96%